2021
DOI: 10.3390/ma14071801
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Various Types of Expandable Graphite and Blackcurrant Pomace on the Properties of Viscoelastic Polyurethane Foams

Abstract: We investigated the effect of the type and amount of expandable graphite (EG) and blackcurrant pomace (BCP) on the flammability, thermal stability, mechanical properties, physical, and chemical structure of viscoelastic polyurethane foams (VEF). For this purpose, the polyurethane foams containing EG, BCP, and EG with BCP were obtained. The content of EG varied in the range of 3–15 per hundred polyols (php), while the BCP content was 30 php. Based on the obtained results, it was found that the additional introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Excellent intumescent coating expands 50 to 200 times, forming a fine-scale multicellular network with cell sizes ranging from 20 to 50 µm and wall thicknesses ranging from 6 to 8 µm [ 82 , 93 ]. Oliwa et al discovered that adding graphite flakes to an intumescent coating could increase flame resistance [ 104 ]. When heated, the flakes expand up to 100 times, resulting in a more effective insulating layer [ 105 ].…”
Section: Intumescent Coatingsmentioning
confidence: 99%
“…Excellent intumescent coating expands 50 to 200 times, forming a fine-scale multicellular network with cell sizes ranging from 20 to 50 µm and wall thicknesses ranging from 6 to 8 µm [ 82 , 93 ]. Oliwa et al discovered that adding graphite flakes to an intumescent coating could increase flame resistance [ 104 ]. When heated, the flakes expand up to 100 times, resulting in a more effective insulating layer [ 105 ].…”
Section: Intumescent Coatingsmentioning
confidence: 99%
“…Secondly, they must not break the balance of the gelling and blowing reactions as this can produce foams with defects and undesirable properties [21]. In the absence of additives, the foam's cells have a symmetrical polyhedral regular shape [21,22]. However, the presence of an additive affects this structure by the formation of a network of hydrogen bonding between the urethane group, urea groups, or the carbonyl groups in the polyurethane network [22].…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of additives, the foam's cells have a symmetrical polyhedral regular shape [21,22]. However, the presence of an additive affects this structure by the formation of a network of hydrogen bonding between the urethane group, urea groups, or the carbonyl groups in the polyurethane network [22]. Wrzesniewska-Tosik et al observed that though adding flame retardant additives improved the fire resistance of the foam, the foam's morphology also changed by a decrease in pore size and an increase in cell wall thickness.…”
Section: Introductionmentioning
confidence: 99%
“…The halogen-free phosphorous-sulphur ionic liquid was successfully added to the matrix of FPUF [ 13 ]. Oliwa et al [ 14 ] investigated the effect of the type and amount of expandable graphite and blackcurrant pomace on the flammability and thermal stability of viscoelastic polyurethane foams. The flame-retardant and smoke-suppressant flexible polyurethane foams were designed and synthesized based on expandable graphite and novel liquid phosphorus-containing polyol [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%